Genetic Convergence and Variation Cooking and Eating Characteristics of Introduced of Six Rice Genotypes (Oryza sativa L.) Using UPOV Guide (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
A laboratory study was conducted at Al-Mishkhab Rice Research Station (Najaf governorate) in 2019 aimed to know the genetic convergence and variation for cooking and eating characteristics of six rice genotypes (Oryza sativa L.) introduced from Iran. They are: (Khazar, Dorfak, Neda, Nemat, Gohar, and Shiroodi), these genotypes were compared with three local rice released are: Anber33, Yasmine, and Furat1 varieties due to its most prevalent in the farmer fields,  and their qualities of aromatic and cooking preferred by the Iraqi consumers.      UPOV description of 7 cooking and eating characteristics were used to directly identify the genetic convergence and variation.     The results indicated that distinguish between the nine rice genotypes and varieties in cooking and eating characteristics. Three distinct characteristics of variation were expressed: the need for rice for water during cooking, taste and flavor after cooking and the palatable taste of cooked rice, while the other characteristics showed a less variation between the genotypes. The data relationship showed a difference between genotypes and varieties, with the kinship degree ranged from (0.0) to (2.0). The relationship showed that there was one close genetic relationship with a distance of (0.0) between Anber 33 and Gohar, and a clear differentiation of the genotypes (Nemat and Shiroodi), which appeared at a distance of (1.0) from the other genotypes. Furat 1 with a distance (1.5) and Khazar with a distance (1.2), which were characterized as separate branch. While the two genotypes (Neda and Dorfak) appeared as a separate group at a distance of (2.0).